2023
DOI: 10.1038/s41598-023-38569-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with myopia in 19-year-old adult men in Korea between 2014 and 2020

Abstract: Numerous environmental factors that influence myopia have been studied, but only few factors have been definitively identified. We examined factors influencing myopia using data from 2014 to 2020 physical examinations received from the Korean Military Manpower Administration. We used the Cochran–Armitage trend test to investigate the annual prevalence of myopia and high myopia. To determine risk factors for myopia, logistic regression was performed. The data of 2,215,126 19-year-old Korean men were examined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Another population study analyzing 24 h urinary sodium excretion found that East Asian countries are also among the highest consumers of dietary sodium [39]. Interestingly, the current myopia prevalence in urban areas of East Asian countries has risen to 80-90% among young adults, and myopia is prevalent in 96.5% of 19-year-old men in Seoul, South Korea [40].…”
Section: Nutritional Epidemiology Of Myopia and Dietary Sodiummentioning
confidence: 99%
“…Another population study analyzing 24 h urinary sodium excretion found that East Asian countries are also among the highest consumers of dietary sodium [39]. Interestingly, the current myopia prevalence in urban areas of East Asian countries has risen to 80-90% among young adults, and myopia is prevalent in 96.5% of 19-year-old men in Seoul, South Korea [40].…”
Section: Nutritional Epidemiology Of Myopia and Dietary Sodiummentioning
confidence: 99%